Reduced ADAMTS13 activity is associated with thrombotic risk in systemic lupus erythematosus. (October 2015) - Martin-Rodriguez, S; Reverter, J C; Tàssies, D; Espinosa, G; Heras, M; Pino, M; Escolar, G; Diaz-Ricart, M
Background: Severe deficiency of ADAMTS13 activity leads to von Willebrand factor (VWF) ultralarge multimers with high affinity for platelets, causing thrombotic thrombocytopenic purpura. Other pathological conditions with moderate ADAMTS13 activity exhibit a thrombotic risk. We examined the ADAMTS13 activity in systemic lupus erythematosus (SLE) and its value as a thrombotic biomarker.Methods: ADAMTS13 activity, VWF antigen and multimeric structure, and vascular cell adhesion molecule 1 (VCAM-1) were measured in plasma samples from 50 SLE patients and 50 healthy donors. Disease activity (systemic lupus erythematosus disease activity index; SLEDAI) and organ damage (systemic lupus international collaborating clinics) scores, thrombotic events, antiphospholipid syndrome (APS) and antiphospholipid antibodies (aPLs) were registered.Results: SLE patients showed decreased ADAMTS13 activity and high VWF levels compared with controls (66 ± 27% vs. 101 ± 8%, P < 0.01, and 325 ± 151% vs. 81 ± 14%, P < 0.001). VCAM-1 levels were higher in SLE patients ( P < 0.05). Considering three groups of SLE patients depending on ADAMTS13 activity (>60%, 60–40% and <40%), comparative analysis showed significant association between ADAMTS13 activity and SLEDAI ( P < 0.05), presence of aPLs ( P < 0.001), APS ( P < 0.01) and thrombotic events ( P < 0.01). Reduced ADAMTS13 activity together with increased VWF levels were especially notable in patients with active disease and with aPLs.Conclusion: ADAMTS13 activity, in combination with other laboratory parameters, could constitute a potential prognostic biomarker of thrombotic risk in SLE.